Fun activities to develop reading skill for young learners - Guarango Fajardo, Zoila Corina; Naula Anguisaca, Blanca Alicia
This research has been developed to emphasize the importance of fun activities in a teaching-learning process. Fun activities are defined as a form of playing with rules, goals, competitions, relaxations, and learning. Teachers can use fun activities as integral part of learning. These forms of activities have many benefits for the teachers as well as the students in improving skills. We can also say that fun activities are an important tool in English classrooms; they are the essential resource to encourage students to develop skills like reading. Students, in this light, forget that they are learning and think of the learning activities as only a fun game thus pressing more attention to the material. The research will also review the effectiveness of different lesson plans as well as how fun activities should be used within the classroom. This investigation contains four lesson plans to work with beginner students from ten to twelve. The activities in the lesson plans are for practicing adjectives, nouns, present tense, and past tense. Two of these lesson plans were applied in Técnico12 de Abril School from Gualaceo with students in eight grades. When applying our research work, the results obtained in the English classroom were very positive. We could see how the fun activities created a motivational environment among the students and the teachers. In addition, the students succeeded in developing more reading skills by using a more enjoyable and interactive means which are games.